Some responsibilities of the parties under the agreement on participation in share construction contracts (Texas Journal of Multidisciplinary Studies, 2022)
The article studies not regulated relations in the contract arising in the field of share participation in construction. Analyzing the legislation related to shared construction, it was concluded that the legislation does not fully disclose the essence of the shared construction agreement.